2016
DOI: 10.1093/hsw/hlw012
|View full text |Cite
|
Sign up to set email alerts
|

Childhood, Adolescent, and Teenage Obesity: Recommendations for Community Initiatives in Central Harlem

Abstract: Because of poverty, the high prevalence of obesity, and the lack of adequate supports, Central Harlem's children, adolescents, and teenagers are at risk for major physiological, psychological, and social issues. This article discusses the public health concerns related to this population, especially the prevalence of obesity. This article identifies the prevalence of illness and obesity in the inner city and stipulates the causes and consequences of obesity among children, adolescents, and teenagers. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Karpati et al (2003) state residents of Harlem have markedly higher rates of illness and mortality when compared to the greater area of New York City. Maidenberg (2016) claims that obesity and diabetes are more prevalent in Harlem due to a high crime rate and lack of funding for physical education in the public school system. Our research adds to the discussion on how some SFD organizations in Harlem are attempting to combat the health, political, and economic disparities that have beset the neighborhood for generations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Karpati et al (2003) state residents of Harlem have markedly higher rates of illness and mortality when compared to the greater area of New York City. Maidenberg (2016) claims that obesity and diabetes are more prevalent in Harlem due to a high crime rate and lack of funding for physical education in the public school system. Our research adds to the discussion on how some SFD organizations in Harlem are attempting to combat the health, political, and economic disparities that have beset the neighborhood for generations.…”
Section: Discussionmentioning
confidence: 99%
“…According to Maidenberg, a high prevalence of poverty and the lack of adequate financial support means that “Harlem’s children, adolescents, and teenagers are at risk for major physiological, psychological, and social issues” (2016: 85). Childhood and adolescent obesity is an epidemic in the United States, especially for urban youth of African American descent (Thorpe et al, 2004).…”
Section: Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals participating in obesity treatment programs have improved their health and adherence to program objectives by surrounding themselves with others who are working toward similar goals (Giannini et al, 2017). By establishing a support group, individuals can improve their health outcomes (Maidenberg, 2016). A 2013 scientific statement from the American Heart Association (AHA) reviewed the role of social networks and the use of social media approaches in childhood obesity prevention and management, and found that social media interventions can be used to build on existing social networks or to build new networks (Li et al, 2013).…”
Section: Researchmentioning
confidence: 99%
“…Some researchers have worked to better understand the factors associated with not having enough food to meet monthly household needs-known as food insecurity (Fitzpatrick & Coleman-Jensen, 2014;Slack & Yoo, 2005;Turney, 2014). Others have suggested the use of macro interventions to combat food access inequalities, including community-based participatory research (Jacobson, 2007) and coalition building (Maidenberg, 2016), to improve food access at the community level. Social work research has also been concerned with the effectiveness of social welfare programs such as SNAP (Issar, 2010;Mills, Dorai-Raj, Peterson, & Alwang, 2001;Mosley & Tiehen, 2004;Zedlewski & Rader, 2005) and WIC (Jacknowitz & Tiehen, 2009) that seek to provide additional resources to vulnerable households.…”
Section: Problemmentioning
confidence: 99%